2015
DOI: 10.1016/j.canep.2015.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and health-related predictors of cervical cancer screening attendance in a Swiss population-based study

Abstract: BACKGROUND: Since the implementation of cervical cancer (CC) screening, incidence and mortality rates have decreased worldwide. Little is known about lifestyle and health-related predictors of cervical cancer screening attendance in Switzerland. Our aim was to examine the relationship between lifestyle and health-related factors and the attendance to CC screening in Switzerland. METHODS: We analyzed data of 20-69 years old women (n=7319) of the Swiss Health Survey (SHS) 2012. Lifestyle factors included body ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 53 publications
2
33
0
1
Order By: Relevance
“…In recent years, studies have shown that the chance of screening for these two diseases is higher among women with a healthy lifestyle [26, 27], which could also explain lower incidence rates and mortality in this patient subset.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, studies have shown that the chance of screening for these two diseases is higher among women with a healthy lifestyle [26, 27], which could also explain lower incidence rates and mortality in this patient subset.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that individuals experiencing psychological distress (PD), such as depression or anxiety, are less likely to participate in cancer screening. According to our in-house, preliminary, systematic review, most population-based studies examining the associations between PD and screening for colorectal, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] breast, 1-6,10,14-21 or cervical cancers 1,3,10,15,[17][18][19][22][23][24] have been conducted in North America or Europe. One meta-analysis reported a significant reduction in mammography screening rates among women with mood disorders.…”
Section: Introductionmentioning
confidence: 99%
“…However, even the percentage of women undergoing a Pap test, which is highly important in the early diagnosis of cervical cancer, is not at the desired level. This percentage is above 60% in developed countries and below 20% in underdeveloped countries [10][11][12] . In our country, on the other hand, 72.6% of women above 15 years of age have never had a Pap test 13 .…”
Section: Introductionmentioning
confidence: 99%